Terrorism Financing Modus Operandi In Indonesia - Ali Masyhar Mursyid; Muhammad Haidar Ghoni; Indah Sri Utari; Aprila Niravita; Muhammad Azzam (Universitas Negeri Semarang, 2025)
The dynamics of radicalism and terrorism in Indonesia never cease. Even at the end of 2024, Densus 88 Antiterror arrested a number of perpetrators involved in various terrorist activities. This shows that radicalism and terrorism continue to develop through small cells that spread radical ideology. And, if we let our guard down, they will certainly carry out acts of terrorism using various schemes. To support these radical-terrorist activities, significant funding is required. There are at least two main channels: legal and illegal. Legal fund-raising by radical terrorist groups is carried out through certain disguised methods, such as donations, charity boxes, and some legal businesses. On the other hand, the illegal channel is known as